TECHNOLOGICAL CHARACTERISTICS OF BREADFRUIT FLOUR (Artocarpus altilis L.) IN THE QUALITY OF GLUTEN-FREE BREAD - Santos, Grazielly Silva dos; Pimenta, Francyne Suzarte; Silva, Alex Sander Lopes da; Matos, Laise Cedraz Pinto; Benevides, Clícia Maria de Jesus (Arquivos de Ciências da Saúde da UNIPAR, 2025)
This study aimed to characterize the physicochemical properties and develop gluten-free breads using breadfruit flour (BFF). Three bread formulations were developed: a control bread (CB) with base flour (BF - composed of rice flour, corn starch, and cassava starch), and two variations with partial replacement of BF by 15% and 25% of BFF designated respectively as BFFB15 and BFFB25. For BFF, particle size, water solubility index (WSI) and water absorption index (WAI) were determined. The proximate composition was determined in the BFF and in the breads, as well as the sensory analysis of the breads. BFF showed that 85.10% of its particles were smaller than 250μm. The WAI (g/g) increased from 1.27 to 4.76, while the WSI (%) decreased from 16.10 to 8.80 as the temperature rose from 30 to 95°C. The contents (g/100g) of the BFF proximate composition were: moisture (3.97±0.20); proteins (2.89±0.08); lipids (0.81±0.10); ash (1.15±0.12); carbohydrates (91.33±0.25), while for CB, BFFB15 and BFFB25 there was a variation in moisture from 47.24±0.21 to 51.88±0.21; proteins (5.29± 0.10 to 5.39±0.11); lipids (4.97±0.07 to 5.40±0.47); ash (0.87±0.06 to 1.29±0.06) and carbohydrates (35.91±0.10 to 42.21±0.07). The data suggest that the breads produced have low lipid content and high mineral content. The weight loss of the breads post-cooking was 6.44 and 6.03%, for BFFB15 and BPFFB25, respectively. Sensory analysis showed that both breads presented good acceptance, with BFFB15 having the highest scores. The BFF proved to be nutritionally viable, and with good acceptability in the products evaluated. It also proved to have important technological characteristics for application in gluten-free bakery products, to promote volume and increase the yield of post-baking doughs.